Exploring the Values of Integration of Islamic and Science Education: A Qualitative Approach in Contemporary Learning at Riau Islands High School - Juni Mahanis; Nunung Witono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore and analyze the values ​​of the integration of Islamic Religious Education (PAI) with science in learning in Senior High Schools (SMA) in the Riau Islands. In the era of globalization and rapid technological advances, it is important for education to integrate religious knowledge and science in order to create students who are not only intellectually intelligent but also have strong characters. The research approach used is qualitative descriptive with a case study method involving in-depth interviews, observations, and documentation studies in several high schools in the Riau Islands. This study found that despite major challenges in terms of limited infrastructure, human resources, and access to technology, the integration of PAI and science can enrich students' understanding of the relationship between religion and science. By integrating science into Islamic teachings, students not only learn scientific knowledge but are also trained to think critically in the context of religion and morals. On the other hand, geographical challenges and limited facilities in the Riau Islands cause gaps in the implementation of this integration. Therefore, this study suggests the need for more adaptive learning strategies, improved teacher training, and the use of mobile technology to overcome these challenges. This research is expected to contribute to the development of a more inclusive and relevant education curriculum, especially in remote areas such as the Riau Islands.